A formalist theatre - Kirby, Michael, 1931-1997 (University of Pennsylvania Press, 1987)
Michael Kirby was the most outspoken exponent of formalist theater and founded the Structuralist Workshop in the 1960s to explore this style of performance. He called it "Structuralist" (capitalizing the term popularized by Levi-Strauss) to make a distinction between his emphasis on spatial and temporal form (i.e. structure) and the historical association of formalism with styles and abstraction. The book is based on articles written over the course of a decade for the Drama Review, a quarterly journal Kirby edited for fourteen years. In Part I, "Formalist Analysis," analytical continua are developed and applied to acting, style, and structure; Kirby devotes Part II, "The Social Context," to an analysis of the current state of criticism, theatre as a political tool, and the current state of the avant-garde; Part III, "Structuralist Theatre," describes performances produced by Kirby under the auspices of his structuralist workshop as well as several Structuralist films.